Brazil : Jobs Report, Volume 1. Policy Briefing - World Bank (Washington, DC, 2013)
This report, conducted jointly by researchers in Brazil and at the World Bank, aims to address the debate on how the Brazilian labor market functions. It does so not by focusing on labor market functioning but on its outcomes. What is central are labor market outcomes, such as adequate employment growth so that job-seekers can find gainful employment, acceptable worker productivity levels that are fairly compensated, and reasonable income security for workers and their households. This report is structured as follows: Chapter 1 argues that labor laws have begun to show signs of obsolescence. Chapter 2 shows this is reflected in deteriorating outcomes. Key indicators--employment growth, labor force participation, unemployment rates, and income security--all point to worsening labor market functioning since the mid-1990s. The report then examines how changed macroeconomic circumstances call for changes in labor market institutions, regulations, and interventions. Using a characterization of the economy in which informality has a central role, Chapter 3 illustrates the correspondence between the three main macroeconomic phenomena of the 1990s--greater openness, stabilization, and fiscal adjustment--and Brazil's labor market priorities. Chapter 4 concludes that the labor market has signaled the shortage of educated workers since the 1990s, and the onus is now on the education and training systems to respond. Analysis of how Brazil's labor market functions in Chapter 5 points to evidence that indicates that Brazil's poorer workers and smaller firms are especially disadvantaged by how the labor market functions. The report identifies three sets of priorities for reform: changes in mandated non-wage benefits and minimum wage setting to price labor correctly and encourage empoloyment growth (Chapter 6), changes in severance legislation and functioning of labor courts to better align incentives and increase productivity (Chapter 7), and improvements in interventions to increase income security for all workers (Chapter 8). Chapter 9 summarizes and highlights the main policy implications. Volume 2 contains in-depth examination of the issues of interest in Brazil and the relevant international experience, on which Chapters 1 through 8 of the first volume are based.